2011
DOI: 10.3758/s13423-011-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Perception of facial expression depends on prior attention

Abstract: Attending versus ignoring a stimulus can later determine how it will be affectively evaluated. Here, we asked whether attentional states could also modulate subsequent sensitivity to facial expressions of emotion. In a dual-task procedure, participants first rapidly searched for a gender-defined face among two briefly displayed neutral faces. Then a test face with the previously attended or ignored face's identity was presented, and participants judged whether it was emotionally expressive (happy, angry, or fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Perhaps, angry faces had greater motivational salience than happy faces in our study because they signal disapproval and carry an implicit instruction to alter behavior or “do better” to avoid unpleasant consequences, as opposed to the approval or signal to maintain current behavioral strategies implied by a smiling face. This motivational interpretation of expression information is consistent with the view that anger in another’s face or gesture activates approach responses (Carver & Harmon-Jones, 2009; Wilkowski & Meier, 2010) and also with a recent finding that an angry but not a happy or fearful expression can overcome attention-induced inhibition that dulls sensitivity to subtle facial expression (Gómez-Cuerva & Raymond, 2011). Additional support for the idea that motivation may play a role in WM was reported by Raymond and Thomas (2012), who showed that stimuli previously associated with high-reward value were better remembered in a WM task than stimuli previously associated with losses or no outcome.…”
Section: Discussionsupporting
confidence: 89%
“…Perhaps, angry faces had greater motivational salience than happy faces in our study because they signal disapproval and carry an implicit instruction to alter behavior or “do better” to avoid unpleasant consequences, as opposed to the approval or signal to maintain current behavioral strategies implied by a smiling face. This motivational interpretation of expression information is consistent with the view that anger in another’s face or gesture activates approach responses (Carver & Harmon-Jones, 2009; Wilkowski & Meier, 2010) and also with a recent finding that an angry but not a happy or fearful expression can overcome attention-induced inhibition that dulls sensitivity to subtle facial expression (Gómez-Cuerva & Raymond, 2011). Additional support for the idea that motivation may play a role in WM was reported by Raymond and Thomas (2012), who showed that stimuli previously associated with high-reward value were better remembered in a WM task than stimuli previously associated with losses or no outcome.…”
Section: Discussionsupporting
confidence: 89%
“…Gomez-Cuerva and colleagues examined whether sensitivity of emotional expressions was influenced by prior attentional state in a dual-task [22]. Their results showed that sensitivity to negative expressions was significantly lower when the same identity with the negative expression was a distractor (to-be-ignored) in the previous trial than when it was a target (to-be-attended).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated that emotion processing was influenced by attention have mostly focused on spatial orientation of attention, for example the dot-probe task [30], visual search task [8], [31] and dual-task paradigm [22]. However, fewer studies have examined whether emotion processing was affected by attention in executive control.…”
Section: Introductionmentioning
confidence: 99%
“…Several variables are known to affect the precision in facial emotion recognition: It is known, for instance, that subjects suffering from schizophrenia, autism, or Alzheimer’s disease frequently exhibit difficulties in recognizing emotional expressions (e.g., Baron-Cohen, Wheelwright, Hill, Raste, & Plumb, 2001; Edwards, Pattison, Jackson, & Wales, 2001; Hargrave, Maddock, & Stone, 2002; Harms, Martin, & Wallace, 2010; Tsoi et al, 2008; Weiss et al, 2008). Other influences on the ability to recognize emotions in faces have been shown, for example, for age (Isaacowitz et al, 2007), gender of the observer or the presented face (McClure, 2000; Pixton, 2011), affective content (Becker & Detweiler-Bedell, 2009; Calvo & Marrero, 2009), saliency of specific facial features (Calvo & Nummenmaa, 2008), or prior attention (Gómez-Cuerva & Raymond, 2011).…”
mentioning
confidence: 99%